2017
DOI: 10.1186/s12909-017-1097-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual class evaluation and effective teaching characteristics in integrated curricula

Abstract: BackgroundIn an integrated curriculum, multiple instructors take part in a course in the form of team teaching. Accordingly, medical schools strive to manage each course run by numerous instructors. As part of the curriculum management, course evaluation is conducted, but a single, retrospective course evaluation does not comprehensively capture student perception of classes by different instructors. This study aimed to demonstrate the need for individual class evaluation, and further to identify teaching char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…These 40 studies reported integrated educational interventions employed across medicine (n=28) [10-12, 16-21, 23-25, 28, 29, 31, 33, 34, 36, 38-41, 44-49], pharmacy (n=11) [13-15, 26, 27, 29, 30, 32, 35, 37, 42],and dentistry (n=1) [22] in institutions worldwide: United States of America (n=14) [11, 13-15, 24-27, 29, 30, 32, 40, 42, 46], India (n=7) [10, 18-20, 28, 33, 41], United Kingdom (n=6) [22,35,37,39,43], Middle East (n=4) [16,17,23,31], the Netherlands (n=4) [31,44,48,49], Belgium (n=2) [45,47], and one from each of: Stockholm [12], Brazil [21], Germany [36], and Korea [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…These 40 studies reported integrated educational interventions employed across medicine (n=28) [10-12, 16-21, 23-25, 28, 29, 31, 33, 34, 36, 38-41, 44-49], pharmacy (n=11) [13-15, 26, 27, 29, 30, 32, 35, 37, 42],and dentistry (n=1) [22] in institutions worldwide: United States of America (n=14) [11, 13-15, 24-27, 29, 30, 32, 40, 42, 46], India (n=7) [10, 18-20, 28, 33, 41], United Kingdom (n=6) [22,35,37,39,43], Middle East (n=4) [16,17,23,31], the Netherlands (n=4) [31,44,48,49], Belgium (n=2) [45,47], and one from each of: Stockholm [12], Brazil [21], Germany [36], and Korea [38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of students experiencing the integrated educational activities was not always described, but where included, cohorts varied from relatively small, approximately 30-40, to very large, approximately 1000-2000 students. Most studies, (n=34) adopted surveys to capture student feedback [10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][34][35][36][37][38][39][43][44][45][46][47][48][49], six studies employed student interviews or focus groups [11,12,27,29,36,37] and 24 assessed student performance at a terminal assessment [10,14,15,17,18,21,[23]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations